Biodegradable Mg-Cu alloy implants with antibacterial activity for the treatment of osteomyelitis: In vitro and in vivo evaluations. (November 2016) - Li, Yang; Liu, Lina; Wan, Peng; Zhai, Zanjing; Mao, Zhenyang; Ouyang, Zhengxiao; Yu, Degang; Sun, Qi; Tan, Lili; Ren, Ling; Zhu, Zhenan; Hao, Yongqiang; et al.
Abstract: Treatment of chronic osteomyelitis (bone infection) remains a clinical challenge; in particular, it requires an implantable material with improved antibacterial activity. Here, we prepared biodegradable magnesium (Mg)-copper (Cu) alloys with different Cu contents (0.05, 0.1, and 0.25 wt%) and assessed their potential for treating methicillin-resistant Staphylococcus aureus -induced osteomyelitis. We evaluated the microstructures, mechanical properties, corrosion behavior, and ion release of the alloys in vitro, and their biocompatibility and antibacterial activity in vitro and in vivo . The antibacterial activity of the Mg-Cu alloys in vitro was demonstrated by microbiological counting assays, bacterial viability assays, biofilm formation observations, and the expression of biofilm, virulence, and antibiotic-resistance associated genes. The antibacterial activity of Mg-Cu alloys in vivo was confirmed by imaging examination, microbiological cultures, and histopathology. The biocompatibility of Mg-Cu alloys was confirmed by cell proliferation, vitality, and morphology assays in vitro and Cu 2+ or Mg 2+ ion assays, blood biochemical tests, and histological evaluation in vivo. The alloy containing 0.25 wt% Cu exhibited the highest antibacterial activity among the tested alloys, with favorable biocompatibility. Collectively, our results indicate the potential utility of Mg-Cu alloy implants with 0.25 wt% Cu in treating orthopedic infections.